(untitled) - Mukti Jaiswal (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Today, the bulk of decisions relating to personal or property rights of the people come not from courts but from administrative agencies exercising judicial power. From early times the administrative and judicial functions were inextricably blended in the organs of government. It was a later development that these powers were separated. Today, there is a revivalism of the past when administration has again come to acquire judicial powers. However, in the context of changed circumstances, purpose and need, it may be regarded as a new development. This new development has led to a host of controversies, and therefore, provides a fascinating pursuit for the writers of administrative law. Everything is going just because of concept of welfare state. But on the other hand misuse of these powers by the government is a matter of concern, and the Exclusion Clause of the law is the prominent reason behind this misuse of powers. This research article is an attempt to find out that to what extent the apex court or common civil court can curb the arbitrariness of the administrative authorities despite of this Exclusion Clause?